2021
DOI: 10.7759/cureus.18447
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression Among Patients With Type 2 Diabetes at King Abdullah Medical City

Abstract: IntroductionDiabetes is one of the most common endocrine diseases worldwide. Type 2 diabetes and depression are commonly comorbid, high-prevalence, chronic disorders. Individuals with diabetes mellitus may have concurrent mental health disorders and are shown to have poorer disease outcomes. However, the evidence for clinical correlation is still unclear. ObjectivesTo find the prevalence of depression among patients with type 2 diabetes at King Abdullah Medical City (KAMC). Materials and methodsA cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Among them, 15 were excluded due to the following reasons: 7 lacked sufficient data to generate reliable risk estimates, and 8 described the relationship between depression and diabetes/diabetes complications ( Fig 1 ). Ultimately, 30 studies were investigated, where 24 were about DN predicting depression [ 18 41 ] and 6 were about depression predicting DN [ 42 47 ] (Tables 1 and 2 ). It was noted that 4 of the final 30 studies reported HR and one reported RR in risk evaluation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 15 were excluded due to the following reasons: 7 lacked sufficient data to generate reliable risk estimates, and 8 described the relationship between depression and diabetes/diabetes complications ( Fig 1 ). Ultimately, 30 studies were investigated, where 24 were about DN predicting depression [ 18 41 ] and 6 were about depression predicting DN [ 42 47 ] (Tables 1 and 2 ). It was noted that 4 of the final 30 studies reported HR and one reported RR in risk evaluation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were from Europe [ 21 , 23 , 28 , 37 , 40 , 46 ], one from Africa [ 29 ], 16 from Asia [ 19 , 20 , 22 , 24 , 26 , 30 33 , 35 , 36 , 38 , 39 , 41 , 45 , 47 ], and 7 from America [ 18 , 25 , 27 , 34 , 42 44 ]. There were 10 prospective cohort studies [ 18 , 22 , 25 , 35 , 37 , 40 , 43 , 44 , 46 , 47 ], 18 cross-sectional studies [ 19 21 , 23 , 26 30 , 32 , 33 , 35 , 36 , 38 , 39 , 41 ], 2 case-control studies [ 23 , 31 ]. The largest number of participants were 933,211, while the longest follow-up time was 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…Depressive symptoms are common in patients with uncontrolled type 2 diabetes who also have neuropathy and retinopathy. Hypertension, cardiovascular disease, and an unhealthy diet have been associated with depression [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another Saudi observational study carried on 267 adults patients with type 2 diabetes seen at King Abdulla Medical City in Mecca, using the Arabic version of the Patients Health Questionnaire -9 (PHQ-9) to asses prevalence of depression, 73% suffered from different degrees of depression;36%, 19.9%, 8.6%, 5.2%, and 3.4% of the participants were suffering from minimal, mild, moderate, moderately severe, and severe depression, respectively, and only neuropathy was a signi cant risk factors of depression (odds ratio = 2.87, 95% CI 1.18-6.97. P = 0.02) (19) .…”
Section: Discussionmentioning
confidence: 89%